2018
DOI: 10.1177/1351010x18790832
|View full text |Cite|
|
Sign up to set email alerts
|

Is the sound environment relevant for how people use common spaces?

Abstract: Rapid and intrusive spatial adjustments in common spaces are increasingly questioned by the awareness of citizens demanding higher quality standards. This study aims to understand the use of common space by identifying how the sound environment affects the functions of space and the interaction with other environmental and spatial variables. Is there a certain sound environment required or that should be avoided when designing a space for a specific activity? In situ evaluations with regular users were collect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…It has been established that primary functions and socio-recreational activities in a given space play a key role in soundscape assessment regarding the perceived appropriateness of the sound environment [27]. To describe the people-place-activity context, some researchers have adopted the concept of a 'sociotope', defined as "the commonly perceived direct use values of a place by a specific culture or group" [28,29], to explore the people-place-activity interaction in soundscapes [30][31][32]. These studies demonstrated significant relationships between the appropriateness of soundscapes and the socio-recreational activities in various urban spaces.…”
Section: Introductionmentioning
confidence: 99%
“…It has been established that primary functions and socio-recreational activities in a given space play a key role in soundscape assessment regarding the perceived appropriateness of the sound environment [27]. To describe the people-place-activity context, some researchers have adopted the concept of a 'sociotope', defined as "the commonly perceived direct use values of a place by a specific culture or group" [28,29], to explore the people-place-activity interaction in soundscapes [30][31][32]. These studies demonstrated significant relationships between the appropriateness of soundscapes and the socio-recreational activities in various urban spaces.…”
Section: Introductionmentioning
confidence: 99%
“…Several authors, such as Raimbault and Dubois (2005), Nielbo, Steele, and Guastavino (2013), Bild et al (2018), Estévez-Mauriz, Forssén, and Dohmen (2018), and Romanowska (2018), have highlighted the significance of the urban contextincluding the function of a place and the corresponding activitiesto soundscape. Activities influence the urban form and mobility patterns (Burton, Jenks, and Williams 2000), and consequently the distribution of sound sources within the city, which would affect the soundscape.…”
Section: Introductionmentioning
confidence: 99%
“…The sensation, interpretations and responses to the perceived acoustic environment play a central role in the concept. In recent studies of soundscapes in outdoor public spaces, activities have been considered as a key role in creating urban soundscapes whilst contextualizing the way people evaluated the perceived sound environment [ 8 , 13 , 14 ]. This dual effect has drawn attention to look at the activity-soundscape relations in spaces [ 15 ].…”
Section: Introductionmentioning
confidence: 99%